2021
DOI: 10.1002/wrna.1704
|View full text |Cite
|
Sign up to set email alerts
|

The “guiding” principles of noncoding RNA function

Abstract: The human genome is pervasively transcribed and yet only a small fraction of these RNAs (less than 2%) are known to code for proteins. The vast majority of the RNAs are classified as noncoding RNAs (ncRNAs) and are further subgrouped as small (shorter than 200 bases) and long noncoding RNAs. The ncRNAs have been identified in all three domains of life and regulate diverse cellular processes through transcriptional and posttranscriptional gene regulation. Most of these RNAs work in conjunction with proteins for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 153 publications
0
24
0
Order By: Relevance
“…RNAs can also interact with other RNAs and several studies have shown these interactions to be crucially involved in the regulation of gene transcription, cell metabolism, and other key cellular functions (Deogharia and Gurha, 2021;Singh et al, 2022;Wang et al, 2022). Despite the fact that a large number of RNA-RNA interactions have been experimentally validated, many more have yet to be identified.…”
Section: Computational Methods For Rna-rna Interactions Predictionmentioning
confidence: 99%
“…RNAs can also interact with other RNAs and several studies have shown these interactions to be crucially involved in the regulation of gene transcription, cell metabolism, and other key cellular functions (Deogharia and Gurha, 2021;Singh et al, 2022;Wang et al, 2022). Despite the fact that a large number of RNA-RNA interactions have been experimentally validated, many more have yet to be identified.…”
Section: Computational Methods For Rna-rna Interactions Predictionmentioning
confidence: 99%
“…Beyond the developments as reviewed in section 2.3, a further level of complexityi.e. the human epigenome and its life-time dynamics in health and cardiovascular disease [84,[146][147][148][149][150][151][152][153][154][155] -emerged as holding promise for possible therapeutic exploitation [114-120, 156, 157]. At the present time, however, the impact of epigenetic drugs upon clinical medicine is still limited as compared to the nucleic acid drugs discussed above.…”
Section: Continuously Emerging New Levels Of Complexity Of the Human ...mentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs) primarily include microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) ( Jusic et al, 2020 ; Deogharia and Gurha 2021 ; Rahimian et al, 2021 ). The ncRNAs bind to multiple molecular targets to form regulatory networks in various biological activities, including initiating specific cellular biological responses, regulating gene expression, intracellular signaling, and epigenetic modifications ( Ding et al, 2021 ; Ducoli and Detmar 2021 ).…”
Section: Introductionmentioning
confidence: 99%